(untitled) (International Educators Conference, 2025)
This study investigates the perceptions of geography students regarding the significance, challenges, and effectiveness of using interactive cartographic tools in geography education. The findings highlight the widespread support for their use, identify key technical and pedagogical challenges, and suggest strategies for more effective integration.